Understanding how ontological conflicts materialize through dialogue between political ontology and Henri Lefebvre’s spatial theories - Lamers, Louise (Alternautas, 2024)
This article explores how Henri Lefebvre’s spatial theories can inform post-development research, particularly into socio-environmental conflicts. Post-development’s politico-ontological branch understands these conflicts as ontological clashes, stemming from the imposition of particular understandings of concepts like ’development’ and ’nature’. The article argues that Lefebvre’s spatial theories constitute a language for grasping the spatial dynamics of these ontological conflicts. The article offers guidance on applying this language by navigating through four key areas: (1) the ontological domain, by first overcoming some problems in Lefebvre’s work through a politico-ontological reading, (2) the methodological domain, by demonstrating how his work provides an analytical framework to dissect the spatial manifestations of conflicts between diverse worlds, (3) the epistemological domain, by highlighting how Lefebvre’s theories give insights into strategies of dominant ontologies to remain in power, (4) the domain of theories of change, by emphasizing Lefebvre’s advocacy for the empowerment of marginalized communities to reclaim agency in shaping their spatial environment. This theoretical effort is then briefly illustrated with tensions that can arise from fortress conservation policies. Given their clear material concerns regarding land use and distribution, it is demonstrated how a PD’s politico-ontological examination of such socio-environmental conflicts can benefit from Lefebvre’s spatial theories.